Manpower, financial, material resources, and participation level in national fitness: a fuzzy-set QCA approach - Xu, Ping; Zhu, Liang; Yang, Liu; Yan, Jin (Frontiers in Public Health, 2024)
Background In the era of economic globalization, major public health events—such as the Ebola epidemic, the avian influenza epidemic, the “SARS” epidemic, and the COVID-19 pandemic—occur more frequently, severely endangering human life safety and health and making global public health governance a major survival issue of universal concern. Therefore, governments have included the improvement of national health in their sustainable development goals, and its important position in global and national health policies has become increasingly prominent. However, the most common non-medical intervention taken by the government is to encourage people to actively participate in physical fitness activities to prevent disease and improve health. Therefore, how to improve the level of participation in national fitness is not only a hot topic in the academic community, but also a work content that governments around the world attach great importance to. Objectives To reveal the complex interaction of the factors affecting the participation level in national fitness and obtain the linkage and adaptation mode of multiple conditions. Study design Starting from the three elements of manpower, financial, material resources, combined with the characteristics of the organizational behavior of local governments in China, this study puts forward an integrated analysis framework to understand the difference of the participation level in national fitness in various provinces and regions. Methods Fuzzy-set Qualitative Comparative Analysis (fsQCA) is used to carry out configuration analysis on the participation level in national fitness in 31 provinces and regions in China. Results First, no single necessary condition can explain the results, whether for high-or low-level national fitness participation. Second, the construction of social sports instructors, public financial support for mass sports, and the supply of sports venues are the core conditions for improving the participation level in national fitness. Third, high-level participation of national fitness is carried out in five ways in China’s provinces. Conclusion These findings enrich the literature on improving the participation level in national fitness, and provide useful practical enlightenment for the local governments to increase the participation level in national fitness.